The theoretical evaluation of saccharin electrochemical detection on cp-based diazonium salts in alkaline media - Романів, Людмила Вікторівна (Journal of Chemical and Pharmaceutical Research, 2017)
The possibility of saccharin electrochemical detection, based on its azo-coupling with CP-based diazonium salts in alkaline media has been evaluated from the theoretical point of view. The correspondent mathematical model has been analyzed by means of linear stability theory and bifurcation analysis. It was shown that the lightly alkaline solutions are favorable for saccharin electrochemical detection, but in strongly alkaline media, the concurrence between the electroanalytical process and hydroxylation of diazonium groups influences strongly on the system´s behavior. The possibility of oscillatory and monotonic instability has been also verified.
Keywords: Intoxication prevention; Saccharin; Conducting polymers; Electrochemical sensors; Azo-coupling: Steady-state stability